Association between Ambient Air Pollution and Hospital Length of Stay among Children with Asthma in South Texas - Juha Baek (International Journal of Environmental Research and Public Health, 2020)
Although hospital length of stay (LOS) has been identified as a proxy measure of healthcare expenditures in the United States, there are limited studies investigating the potentially important association between outdoor air pollution and LOS for pediatric asthma. This study aims to examine the effect of ambient air pollution on LOS among children with asthma in South Texas. It included retrospective data on 711 children aged 5–18 years old admitted for asthma to a pediatric tertiary care hospital in South Texas between 2010 and 2014. Air pollution data including particulate matter (PM2.5) and ozone were collected from the U.S. Centers for Disease Control and Prevention. The multivariate binomial logistic regression analyses were performed to determine the association between each air pollutant and LOS, controlling for confounders. The regression models showed the increased ozone level was significantly associated with prolonged LOS in the single- and two-pollutant models (p < 0.05). Furthermore, in the age-stratified models, PM2.5 was positively associated with LOS among children aged 5–11 years old (p < 0.05). In conclusion, this study revealed a concerning association between ambient air pollution and LOS for pediatric asthma in South Texas.